Analisis Kualitatif Tentang Dampak Cancel order dan Ratting Customer terhadap Kinerja, Performa dan Pendapatan Ojek Online (Gojek) di Slawi - Sri Rahayu (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to qualitatively analyze the impact of order cancellations and customer ratings on the performance, performance, and income of online motorcycle taxi (Gojek) drivers in the Slawi region. The research method used a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation of a number of active drivers. The results show that the high rate of order cancellations, both from customers and the system, negatively impacts driver income stability and reduces work time efficiency. Furthermore, customer ratings play a crucial role in determining driver access to orders, incentives, and account sustainability. Drivers with low ratings tend to experience decreased performance due to limited opportunities to receive orders. On the other hand, the pressure to maintain high ratings also affects drivers' psychological state and work strategies. This study concludes that order cancellations and customer ratings are crucial factors that are interrelated in influencing the work quality and welfare of online motorcycle taxi drivers. Therefore, fairer and more transparent platform policies are needed to maintain a balance between customer satisfaction and driver protection.